Handling The Crime of Manipulating Children's Photos That Violate The Morality of Studies at The Cirebon City Police - Ria Febriyanti; Siska Karina; Waluyadi Waluyadi (Jurnal Legisci, 2026)
Background. The development of information technology and Artificial Intelligence (AI) has given rise to various forms of cybercrime, one of which is the criminal act of manipulating indecent images of children. Aims. This study aims to identify the modus operandi and the handling of criminal acts involving the manipulation of indecent images of children by the police. The research method employed is normative legal research using statutory, conceptual, and case approaches. The data were obtained through a literature review supported by interview results and case documents as supplementary analytical materials. Result. The findings indicate that the modus operandi involves obtaining victims' photographs through social media or other digital platforms, which are then manipulated using Artificial Intelligence-based applications to produce indecent content. Such actions constitute a form of cybercrime that violates moral norms and may be categorized as digital pornography. The handling of these cases by the police includes receiving reports, collecting evidence, examining witnesses, and coordinating with information technology experts. Nevertheless, the handling process continues to face obstacles, including limited human resources in the field of digital forensics and inadequate supporting facilities. Conclusion. Juridically, the handling of these cases has referred to Law Number 1 of 2024 concerning Electronic Information and Transactions, Law Number 44 of 2008 concerning Pornography, and Law Number 35 of 2014 concerning Child Protection.